Online community management for dummies - Ng, Deborah (--For dummies., 2011)
Learn to manage, grow, and communicate with your online community Online community management is a growing profession and companies are investing in online communities in order to gain consumer insights into products and to test new products. An effective and dedicated community manager is essential to engage and manage a successful online consumer community. This straightforward-but-fun guide shows you how to effectively manage, grow, and communicate with your online community. Clear coverage shares tips for dealing with customers and fans through Twitter, Facebook, forums, and blogs. A pract.